2021
DOI: 10.1096/fj.202002333rr
|View full text |Cite
|
Sign up to set email alerts
|

Membrane hyperpolarization abolishes calcium oscillations that prevent induced acrosomal exocytosis in human sperm

Abstract: Sperm capacitation is essential to gain fertilizing capacity. During this process, a series of biochemical and physiological modifications occur that allow sperm to undergo acrosomal exocytosis (AE). At the molecular level, hyperpolarization of the sperm membrane potential (Em) takes place during capacitation. This study shows that human sperm incubated under conditions that do not support capacitation (NC) can become ready for an agonist stimulated AE by pharmacologically inducing Em hyperpolarization with Va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 60 publications
1
20
0
Order By: Relevance
“…In vitro, the incubation of human sperm in capacitating conditions is associated with changes in the plasma membrane [ 87 ], protein phosphorylation [ 88 ], membrane potential (Vm) hyperpolarization [ 89 ] and elevation of the [Ca 2+ ]i and pHi. All are necessary for cells to undergo the AR [ 47 , 90 ]. The AR is more likely to be suppressed in cells which exhibit Vm and pH-dependent [Ca 2+ ]i oscillations [ 90 , 91 ], which occur spontaneously in ~35% of the capacitated cells [ 47 ], and ~20% develop oscillations in response to the P4 [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro, the incubation of human sperm in capacitating conditions is associated with changes in the plasma membrane [ 87 ], protein phosphorylation [ 88 ], membrane potential (Vm) hyperpolarization [ 89 ] and elevation of the [Ca 2+ ]i and pHi. All are necessary for cells to undergo the AR [ 47 , 90 ]. The AR is more likely to be suppressed in cells which exhibit Vm and pH-dependent [Ca 2+ ]i oscillations [ 90 , 91 ], which occur spontaneously in ~35% of the capacitated cells [ 47 ], and ~20% develop oscillations in response to the P4 [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…All are necessary for cells to undergo the AR [ 47 , 90 ]. The AR is more likely to be suppressed in cells which exhibit Vm and pH-dependent [Ca 2+ ]i oscillations [ 90 , 91 ], which occur spontaneously in ~35% of the capacitated cells [ 47 ], and ~20% develop oscillations in response to the P4 [ 30 ]. The Vm and pHi changes associated with capacitation are heterogeneous [ 89 , 92 , 93 , 94 , 95 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, FBC in live sperm itself emerges as a limitless and therefore valuable tool. Considering only the proper Frontiers in Cell and Developmental Biology frontiersin.org combination of fluorophores, this system could be applied in the future to determine novel blockers of acrosome reaction (by using for example the mouse model with EGFP in their acrosomes (Hasuwa et al, 2010) or FM4-64 when the desired extension to humans is performed (Balestrini et al, 2021)), intracellular [Ca 2+ ] i increase (Fluo-4, Fluo-3 or Fura), intracellular pH alkalinization (BCECF), as well as other biochemical and/or functional events associated with sperm capacitation.…”
Section: Discussionmentioning
confidence: 99%
“…Our model could be adapted and applied to human sperm by adjusting the activation curves of SLO3 and taking into account the voltage-gated hydrogen channel 1, HV1, which has been shown to be the dominant proton conductance in human sperm (Lishko et al, 2010). However, as this transporter is not activated by hyperpolarization as it is the case for sNHE, another feedback loop could take place, between hSLO3 and Catsper, as it has been shown that the variations in hyperpolarization and intracellular calcium concentration of human spermatozoa are interconnected during capacitation (Balestrini et al, 2021). The proposed minimal model has allowed us to identify the core molecular mechanism which is likely to control murine sperm capacitation.…”
Section: Discussionmentioning
confidence: 99%